Genetic damage and potential mechanism exploration under different air pollution patterns by multi-omics. (December 2022) - Xu, Jiayu; Zhang, Qiaojian; Su, Zekang; Liu, Yu; Yan, Tenglong; Zhang, Yali; Wang, Tiancheng; Wei, Xuetao; Chen, Zhangjian; Hu, Guiping; Chen, Tian; Jia, Guang
Graphical abstract: Highlights: The mode of DNA damage action was dependent on the exposed modes. DNA damage caused by high-level short-term PM2.5 can be alleviated by natural repair. RAD51 hypermethylation caused by PM2.5 might be the epigenetic mechanism for DSBs. MiRNAs could regulate the expression level of repair genes in lungs. Abstract: Ambient air pollution was classified as carcinogenic to humans (Group 1) for lung cancer. DNA damage was an important first step in the process of carcinogenesis, and could also be induced by air pollution. In this study, intratracheal instillation and real-time air exposure system were combined to establish SHP (short-term high-level PM2.5 ) and LLPO (long-term low-level PM2.5 and O3 ) exposure patterns, respectively. Hierarchical levels of genetic biomarkers were analyzed to explore DNA damage effects in rats. Representative DNA repair genes from different repair pathways were selected to explore the relative expression levels. The methylation level of differentially expressed repair genes were also determined. Besides, miRNA sequencing and non-targeted metabolomic analysis were performed in rat lungs. KEGG and multi-omics analysis were used to explore the potential mechanism of genetic damage under different air pollution patterns. We found that LLPO exposure induced DSBs and chromosome damage. SHP exposure could induce DSBs and DNA oxidative damage, and the effects of genetic damage under this pollution pattern could be repaired by natural repair. Repair genes involved in two pattern were different. SHP exposure could induce higher methylation levels of RAD51, which might be a potential epigenetic mechanism for high-level PM2.5 induced down-regulated expression of RAD51 and DSBs. Besides, 29 overlapped alterations in metabolic pathways were identified by metabolomic and miRNA sequencing, including purine metabolism and pyrimidine metabolism after LLPO exposure. Differential miRNAs expression in lung tissue were associated with apoptosis, DNA damage and damage repair. We concluded that under different air pollution patterns, DNA damage biomarkers and activated targets of DNA damage repair network were both different. The genetic damage effects caused by high-level short-term PM2.5 can be alleviated by natural repair. We provided possible mechanisms by multi-omics which could explain the increased carcinogenic risk caused by air pollution.